2018
DOI: 10.1093/neuros/nyy082
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery for Intracranial Ependymomas: An International Multicenter Study

Abstract: SRS provides another management option for residual or recurrent progressive intracranial ependymoma patients who have failed initial surgery and RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
1
18
1
Order By: Relevance
“…With most of the available SRS and SBRT data for ependymomas focusing on intracranial lesions, outcome data for spinal treatments remain sparse ( 10 12 , 15 18 ). Moreover, the majority of previous studies on SRS utilized GammaKnife (GK)- or conventional linear accelerator (LINAC)-based radiosurgery ( 11 , 12 , 15 17 , 19 21 ). Previous studies analyzing SRS and SBRT for intracranial and spinal ependymal tumors observed LC rates typically ranging between 60 and 80% ( 10 , 13 , 15 , 16 , 19 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With most of the available SRS and SBRT data for ependymomas focusing on intracranial lesions, outcome data for spinal treatments remain sparse ( 10 12 , 15 18 ). Moreover, the majority of previous studies on SRS utilized GammaKnife (GK)- or conventional linear accelerator (LINAC)-based radiosurgery ( 11 , 12 , 15 17 , 19 21 ). Previous studies analyzing SRS and SBRT for intracranial and spinal ependymal tumors observed LC rates typically ranging between 60 and 80% ( 10 , 13 , 15 , 16 , 19 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the recent identification of these genetic parameters and the rarity of the tumor, large prospective validations are lacking ( 1 , 6 , 7 ). Previous studies identified differing predictors of OS and progression-free survival (PFS), including the extent of first surgical resection, WHO grade III, intracranial tumor location as well as age, gender and tumor volume at the time of reirradiation ( 11 , 27 , 28 ). Our study cohort mainly consisted of adult patients (83%), with most of them suffering from a primary spinal ependymoma (75%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This marginal advantage of combined plans over VMAT plans should be weighed against the more complex and costly course of CyberKnife plans, and should be investigated in large clinical trials to prove its clinical benefit. Variable studies discussed the use of stereotactic radiosurgery and fractionated stereotactic radiotherapy in ependymoma cases [25][26][27] . Kano and colleagues reported the results of salvaging recurrent/residual ependymoma cases post-surgical excision and RT using stereotactic radiosurgery 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Variable studies discussed the use of stereotactic radiosurgery and fractionated stereotactic radiotherapy in ependymoma cases [25][26][27] . Kano and colleagues reported the results of salvaging recurrent/residual ependymoma cases post-surgical excision and RT using stereotactic radiosurgery 25 . In their analysis, the 5-year OS rate for pediatric patients was 38.5% and patients with age < 18 years had significantly worse local control rate compared to older patients (p=0.014).…”
Section: Discussionmentioning
confidence: 99%